Development of a discharge readiness report within the electronic health record—A discharge planning tool. Issue 8 (14th May 2014) - Tyler, Amy; Boyer, Ann; Martin, Sara; Neiman, Jenae; Bakel, Leigh Anne; Brittan, Mark
<x xml:space="preserve">Abstract</x> BACKGROUND With increasingly complex pediatric inpatients, efficient and effective hospital discharge requires optimal interdisciplinary care coordination and communication. We describe the development of a discharge readiness report (DRR) for the electronic health record (EHR), an integrated summary of discharge‐related information organized into a highly visible and easily accessible report. METHODS We used interviews and process mapping to understand the roles of all disciplines involved in discharge planning and identified key drivers affecting our aim of designing a discharge tool in the EHR. Based on identified key drivers, we designed the DRR and made changes to the report using rapid improvement cycles. The final report includes information necessary for discharge planning organized into 4 domains: potential barriers to discharge, transitional care, home care, and discharge criteria. RESULTS The DRR was activated in June 2012. As planned, the final product incorporated previously existing discharge‐related information from within the EHR, organized into 1 report. Shortly after its introduction, the DRR was included in daily care coordination rounds (CCRs) for medical and medical subspecialty patients. End users found the report to be completely populated and accurate. We measured time to completion of CCRs and found no difference between duration of CCRs pre‐ and postuse of the DRR. CONCLUSIONS Given widespread adoption, EHRs should be optimized to improve healthcare delivery. A discharge planning tool in the EHR may improve the efficiency and effectiveness of care transitions by allowing for proactive discharge planning and improved interdisciplinary communication. Journal of Hospital Medicine 2014;9:533–539. © 2014 Society of Hospital Medicine